Pesan Motivasi Pada Lirik Lagu "Idgitaf - Berahir Diaku" Tentang Kehidupan Sandwich Genaration Yang Sering Menjadi Sandaran Bagi Orang Lain, Namun Bingung Harus Bersandar Pada Siapa - Zannah, Nurul; Lestari, Putri Indah; Sinta, Elvita Dwi; Hakim, M.Farhan Al; Yudha, Sandy (Jurnal Ilmu Sosial, Humaniora dan Seni, 2025)
The sandwich generation refers to individuals who face dual responsibilities of caring for aging parents while also supporting children or other family members who still require assistance. This phenomenon often results in emotional, financial, and social pressures, making the sandwich generation a support system for many, yet leaving them uncertain about where to seek support themselves. This article analyzes motivational messages in Idgitaf's song "Berakhir di Aku," which represents the internal struggles of the sandwich generation. This study employs a descriptive qualitative method using Miles and Huberman's content analysis technique to reveal the deeper meaning behind the song's lyrics. The results highlight how the song portrays the heavy burdens of the sandwich generation through meaningful and emotional lyrics. The motivational messages emphasize the importance of balancing responsibilities to others while prioritizing self-care. Furthermore, the song encourages the sandwich generation to seek emotional support in facing life’s pressures.